The Berenstain bears get stage fright - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random, 1986)
Sister Bear worries about her lines in the school play while Brother Bear has no fear. Guess who forgets the lines during the performance?
AD 580
Adult 580
Keywords: Fear -- Fiction; Bears -- Fiction; Theater -- Fiction